Oxygen and hydrogen profiles and electrical properties of unintentionally doped gallium nitride grown by hydride vapor phase epitaxy. Issue 6 (June 2015) - Garbe, Valentin; Abendroth, Barbara; Stöcker, Hartmut; Gavrilov, Arkadi; Cohen‐Elias, Doron; Mehari, Shlomo; Ritter, Dan; Meyer, Dirk C.
<x xml:space="preserve">Abstract</x> As a consequence of the growth process, undoped commercially available GaN epi layers possess unintentionally incorporated dopants. Electrical and optical methods reveal the doping level and mobility profile which correlates to oxygen impurity distribution and lattice strain